Drone Cinematography Visualization in Tourism Content in Yogyakarta (Vintage Pixel Case Study) - Umar Shiddiq; Budi Dwi Arifianto (Jogjakarta Communication Conference (JCC), 2026)
This study is motivated by the increasing use of drone videos in tourism promotional content in Yogyakarta. This development indicates that aerial visuals are becoming increasingly dominant in digital tourism content production. This study aims to provide evidence that the trend of drone cinematography in Yogyakarta is growing, by taking a case study of Vintage Pixel production house as a representation of a production practice that consistently utilizes drone technology. This study employs a qualitative approach with a case study method. Data were collected through observation of tourism promotional videos uploaded on Vintage Pixel’s Instagram account, interviews with the director, and documentation studies of the produced works. The analysis focuses on identifying the use of drone camera movement features applied to implement specific cinematographic techniques in tourism content. The results show three main findings: the use of the dolly in feature to build focus and dramatic effect, the circle feature to emphasize objects as points of interest through circular movement, and the reveal shot feature to gradually expose the landscape. These three features are consistently used across various analyzed tourism content productions. The findings indicate that the use of drone features is not random, but structured and repetitive as part of a visual strategy. Thus, Vintage Pixel’s production practices can be understood as evidence of the strengthening trend of drone cinematography in tourism promotion in Yogyakarta.